miRNA changes associated with differentiation of human embryonic stem cells into human retinal ganglion cells - Maryam Esmaeili; Daniel A. Smith; Ben Mead (Scientific Reports)
Abstract miRNA, short non-coding RNA, are rapidly emerging as important regulators in cell homeostasis, as well as potential players in cellular degeneration. The latter has led to interest in them as both biomarkers and as potential therapeutics. Retinal ganglion cells (RGC), whose axons connect the eye to the brain, are central nervous system cells of great interest, yet their study is largely restricted to animals due to the difficulty in obtaining healthy human RGC. Using a CRISPR/Cas9-based reporter embryonic stem cell line, human RGC were generated and their miRNA profile characterized using NanoString miRNA assays. We identified a variety of retinal specific miRNA upregulated in ESC-derived RGC, with half of the most abundant miRNA also detectable in purified rat RGC. Several miRNA were however identified to be unique to RGC from human. The findings show which miRNA are abundant in RGC and the limited congruence with animal derived RGC. These data could be used to understand miRNA’s role in RGC function, as well as potential biomarkers or therapies in retinal diseases involving RGC degeneration.